Optimization of the distribution logistics network: A case study of the metalworking industry in Colombia (2022)
Logistics management is a key factor for business competitiveness because of the variety of strategies avai lable to improve the distribution of goods through the supply chain, enabling the optimization of the resources assigned to this effect. A key aspect for good logistics management is the distribution network, where the location of the network components plays a key role, especially in the case of distribution centers, which are platforms through which the goods received from factories or suppliers are redistributed to the various points of sale. In the above context, this case study proposes a solution for selecting two locations from among four possible sites for construction of distribution centers for a company in the metalworking industry, aimed at minimizing operating costs through the design of a logistics distribution network, using as a tool the GUSEK software. To this effect, the aspects taken into consideration include vehicle capacity, the costs associated with opening a distribution center, types and volume of the products to be shipped, costs associated with the travel distances, the production c apacity of the factories, and customer demand, among others. Execution of the model produces the best locations for the distribution centers and the types of vehicles to be used based on their capacity and the optimal routes for transporting a company’s goods